Pristimerin Inhibits MMP-9 Expression and Cell Migration Through Attenuating NOX/ROS-Dependent NF-κB Activation in Rat Brain Astrocytes Challenged with LPS - Yang CC; Hsiao LD; Tseng HC; Kuo CM; Yang CM (Dove Medical Press, 2020)
Chien-Chung Yang,1,2 Li-Der Hsiao,3 Hui-Ching Tseng,3 Ching-Ming Kuo,3 Chuen-Mao Yang3,4 1Department of Traditional Chinese Medicine, Chang Gung Memorial Hospital at Tao-Yuan, Tao-Yuan 33302, Taiwan; 2School of Traditional Chinese Medicine, College of Medicine, Chang Gung University, Tao-Yuan 33302, Taiwan; 3Department of Pharmacology, College of Medicine, China Medical University, Taichung 40402, Taiwan; 4Department of Post-Baccalaureate Veterinary Medicine, College of Medical and Health Science, Asia University, Taichung 41354, TaiwanCorrespondence: Chuen-Mao Yang Tel +886 4-22053366 (Ext. 2229)Email chuenmao@mail.cmu.edu.twPurpose: Neuroinflammation plays a crucial role in neurodegenerative diseases. Matrix metalloproteinases (MMPs) are a landmark of neuroinflammation. Lipopolysaccharide (LPS) has been demonstrated to induce MMP-9 expression. The mechanisms underlying LPS-induced MMP-9 expression have not been completely elucidated in astrocytes. Nuclear factor-kappaB (NF-κB) is well known as one of the crucial transcription factors in MMP-9 induction. Moreover, reactive oxygen species (ROS) could be an important mediator of neuroinflammation. Here, we differentiated whether ROS and NF-κB contributed to LPS-mediated MMP-9 expression in rat brain astrocytes (RBA-1). Besides, pristimerin has been revealed to possess antioxidant and anti-inflammatory effects. We also evaluated the effects of pristimerin on LPS-induced inflammatory responses.Methods: RBA-1 cells were used for analyses. Pharmacological inhibitors and siRNAs were used to evaluate the signaling pathway. Western blotting and gelatin zymography were conducted to evaluate protein and MMP-9 expression, respectively. Real-time PCR was for mRNA expression. Wound healing assay was for cell migration. 2ʹ,7ʹ-dichlorodihydrofluorescein diacetate (H2DCF-DA) and dihydroethidium (DHE) staining were for ROS generation. Immunofluorescence staining was conducted to assess NF-κB p65. Promoter-reporter gene assay and chromatin immunoprecipitation (ChIP) assay were used to detect promoter activity and the association of nuclear proteins with the promoter.Results: Our results showed that the increased level of ROS generation was attenuated by edaravone (a ROS scavenger), apocynin (APO; an inhibitor of p47Phox), diphenyleneiodonium (DPI; an inhibitor of NOX), and pristimerin in RBA-1 cells exposed to LPS. Besides, pretreatment with APO, DPI, edaravone, Bay11-7082, and pristimerin also inhibited the phosphorylation, nuclear translocation, promoter binding activity of NF-κB p65 as well as upregulation of MMP-9 expression-mediated cell migration in RBA-1 cells challenged with LPS.Conclusion: These results suggested that LPS enhances the upregulation of MMP-9 through nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)/ROS-dependent NF-κB activity. These results also provide new insights into the mechanisms by which pristimerin attenuates LPS-mediated MMP-9 expression and neuroinflammatory responses.Keywords: neuroinflammation, NOX, ROS, LPS, MMP-9, pristimerin, astrocytes